Writing Reflective Journal and Corrective Feedback: The Endeavors to Increase Students’ Physics Achievement of Dynamic Fluids - Tomo Djudin (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
This study aims to determine the effectiveness of teacher’ corrective feedback based on students reflective journal in the learning of dynamic fluids. The research method employed an experimental method with quasi-experimental nonequivalent control group design. The sample of eleventh grade of public senior high school SMAN 8 Pontianak consist of the XI-4 class as experimental group and the XI-3 class as control group were drawn by using intact group random sampling technique. The achievement test consists of 25 multiple choice questions embracing factual, conceptual, and procedural knowledge was administered. After manipulating the treatment, it is concluded that the average of achievement of experimental group (64.27) and control group (52.13) were significant difference (p < 0.05). In addition, the extent of effectiveness of the treatment was in high category (ES = 1.02). The treatment should be provided to increase students’ learning outcomes of any teaching-learning materials.